2020
DOI: 10.1007/s42452-020-3043-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on energy consumption in rotating machinery caused by misalignment

Abstract: In this study we present an evaluation of the energy consumption in the case of shaft misalignment. Misalignment is one of the most common defects in rotating machinery that causes noticeable losses of energy. The proposed methodology focuses on finding a correlation between vibration level and energy consumption for different degrees of misalignment. In fact, the monitoring of energy consumption became a necessity for industries for the implementation of the appropriate maintenance strategy. In order to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Therefore, a large number of studies have focused precisely on investigating this area [48,[55][56][57][58][59]. The aging of energy infrastructure is a global challenge, so the scientific search for and active action in technologies' improvement that is capable of affecting rates of depreciation and reducing operating costs will give a significant boost not only to the oil and gas industry, but to all sectors [60][61][62].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a large number of studies have focused precisely on investigating this area [48,[55][56][57][58][59]. The aging of energy infrastructure is a global challenge, so the scientific search for and active action in technologies' improvement that is capable of affecting rates of depreciation and reducing operating costs will give a significant boost not only to the oil and gas industry, but to all sectors [60][61][62].…”
Section: Methodsmentioning
confidence: 99%
“…For example, the motor shaft's misalignment can cause 3% of energy losses, while the unbalance contributes to 1% of energy losses (Gaberson, 1996). In addition, the parallel misalignment has more considerable energy losses than angular misalignment (Abouelanouar et al ., 2020). Another study revealed that an unbalanced pump reduced the flow rate by 2.4% and the pump's power by 5% (Taneja, 2013).…”
Section: Maintenance Strategies and Energy Efficiencymentioning
confidence: 99%
“…The results show that the closer the blade is to the shell, the more serious the friction is. Abouelanouar et al [26] investigated the effect of misalignment on energy consumption using vibration analysis.…”
Section: Introductionmentioning
confidence: 99%